2022
DOI: 10.1002/anie.202210572
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Removal of the Greenhouse Gas Nitrous Oxide by Liposomal Microreactors

Abstract: Nitrous oxide (N 2 O) is a potent greenhouse and ozone-reactive gas for which emissions are growing rapidly due to increasingly intensive agriculture. Synthetic catalysts for N 2 O decomposition typically contain precious metals and/or operate at elevated temperatures driving a desire for more sustainable alternatives. Here we demonstrate self-assembly of liposomal microreactors enabling catalytic reduction of N 2 O to the climate neutral product N 2 . Photoexcitation of graphitic Ndoped carbon dots delivers e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“… a Liposome embedding a synthetic molecular CPQ triad, quinone and a F 0 -F 1 -ATP synthase for electron and proton transfer across the membrane with concomitant pH gradient generation coupled to the synthesis of ATP reported by A. Moore et al, 96 ( b ) proteoliposome embedding MtrCAB from S. oneidensis MR-1 and encapsulated N 2 O reductase for electron transfer across membrane with N 2 O-to-N 2 reduction reported by J. N. Butt et al, 58 ( c ) polymersome embedding donor and acceptor molecules at each domain of the membrane for transmembrane energy transfer reported by Y. Zheng, Y. Zhou et al, 119 ( d ) polymersome with embedded bacteriorhodopsin a F 0 -F 1 -ATP synthase for transmembrane proton transfer coupled to ATP synthesis reported by T. Vidaković-Koch et al, 99 ( e ) liposome containing a Ru-PS and a Ru-WOC for light-driven WO reported by L. Sun, B. König et al, 127 ( f ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by B. König et al, 132 ( g ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by S. Bonnet et al, 130 ( h ) liposome with a Ru-PS and a CoPc-CO 2 RC for light-driven CO 2 reduction to CO reported by L. Hammarström, E. Reisner et al, 93 ( i ) liposome with a HER-MOF embedded in the hydrophobic membrane and an encapsulated WO-MOF for overall light-driven WS reported by W. Lin, C. Wang et al 140 . …”
Section: Artificial Systems For Electron Proton and Energy Transfer A...mentioning
confidence: 98%
See 4 more Smart Citations
“… a Liposome embedding a synthetic molecular CPQ triad, quinone and a F 0 -F 1 -ATP synthase for electron and proton transfer across the membrane with concomitant pH gradient generation coupled to the synthesis of ATP reported by A. Moore et al, 96 ( b ) proteoliposome embedding MtrCAB from S. oneidensis MR-1 and encapsulated N 2 O reductase for electron transfer across membrane with N 2 O-to-N 2 reduction reported by J. N. Butt et al, 58 ( c ) polymersome embedding donor and acceptor molecules at each domain of the membrane for transmembrane energy transfer reported by Y. Zheng, Y. Zhou et al, 119 ( d ) polymersome with embedded bacteriorhodopsin a F 0 -F 1 -ATP synthase for transmembrane proton transfer coupled to ATP synthesis reported by T. Vidaković-Koch et al, 99 ( e ) liposome containing a Ru-PS and a Ru-WOC for light-driven WO reported by L. Sun, B. König et al, 127 ( f ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by B. König et al, 132 ( g ) liposome with a Ru-PS and a Co-HEC for light-driven HER reported by S. Bonnet et al, 130 ( h ) liposome with a Ru-PS and a CoPc-CO 2 RC for light-driven CO 2 reduction to CO reported by L. Hammarström, E. Reisner et al, 93 ( i ) liposome with a HER-MOF embedded in the hydrophobic membrane and an encapsulated WO-MOF for overall light-driven WS reported by W. Lin, C. Wang et al 140 . …”
Section: Artificial Systems For Electron Proton and Energy Transfer A...mentioning
confidence: 98%
“…Moreover, in the recent years artificial vesicles have gained increasing interest to study the encapsulation of different biologic or synthetic catalysts and separate reactivity, with the potential to create very complex catalytic systems with synchronised reactivity towards chemical production but also in the field of energy 7 17 . Indeed, those artificial systems can be used as simplified model systems to study different processes in the membrane and at interfaces, such as vectorial electron transport, utilization of proton gradients as source of energy and transport of electrons, energy vectors and small molecules across membranes, relevant processes for AP 9 , 10 , 16 , 17 , 42 , 46 , 49 , 58 62 .…”
Section: Common Vesicle-based Scaffolds Used As Biomimetic Microenvir...mentioning
confidence: 99%
See 3 more Smart Citations